AVALIAÇÃO DA IMPLANTAÇÃO DA REFERÊNCIA E CONTRA-REFERÊNCIA DE CONSULTAS ESPECIALIZADAS NO SISTEMA MUNICIPAL DE SAÚDE DE ALFENAS-MG - Rodrigues, Ludmila Barbosa Bandeira (2009)
Since the creation of the Unified Health System, through the promulgation of Brazilian Federal Constitution in 1988, the building process of regionalization and prioritization of health states needs to create mechanisms to ensure coordination between health services in order to establish it as a flow of users in a flexible and dynamic process, called the reference and counter reference. This study aimed to evaluate the implementation of the reference and counter-reference in specialized clinics of the Municipal Health System at Alfenas-MG, from the experience of the practice. This is a qualitative and quantitative descriptive study of the epidemiological type of cross-design. Initially, a review was conducted on the historical process of building the Unified Health System - SUS and the meaning of the reference system and counter-reference in this context. Next step was performed to collect data which used the chips to the routing specialist appointments used by the Municipal Health Department of Alfenas MG and the questionnaires to medical professionals. The results allowed to infer that, although under the organizing principles of SUS, the system of reference and counter reference, is still immature. However, the majority of the medical professionals agree to the necessity of its implantation by means of a computerized system for the information socialization of the attendance given to the user on different attention points and to speed the flow and reverse-flow of the user in the health attention net.